2007
DOI: 10.1093/eurheartj/ehm397
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative cooled-tip radiofrequency linear atrial ablation to treat permanent atrial fibrillation

Abstract: SICTRA safely and effectively restores stable SR in 78% of patients with permanent AF undergoing open-heart surgery. Rhythm outcome is not influenced by treatment of the right atrium. Sustained regular atrial arrhythmia with the need for invasive treatment strategies occurs in 4% although intra-operative ablation lesions are often non-transmural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 22 publications
(56 reference statements)
0
36
0
1
Order By: Relevance
“…Although successful restoration of SR has been identified to increase quality of life and survival (Raanani et al 2001; Deneke et al 2007), the results of surgical cardioversion were controversial in MV patients with permanent AF (Chua et al 1994; Large et al 1997; Jessurun et al 2000; Raine et al 2004). The patients with early recurrence of AF have more advanced pathological changes in the atria and may be good candidates for concomitant anti-AF procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although successful restoration of SR has been identified to increase quality of life and survival (Raanani et al 2001; Deneke et al 2007), the results of surgical cardioversion were controversial in MV patients with permanent AF (Chua et al 1994; Large et al 1997; Jessurun et al 2000; Raine et al 2004). The patients with early recurrence of AF have more advanced pathological changes in the atria and may be good candidates for concomitant anti-AF procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Because of limited success of electrical- and/or drug-induced conversion, concomitant maze procedure and intraoperative radiofrequency ablation have been used during the past two decades (Raanani et al 2001; Deneke et al 2007). However, it remains a significant concern for the inevitable risk of perioperative complications and uncertainty regarding atrial mechanical function (Cox et al 2000; Boyd et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limited success of electrical and/or drug-induced conversion, concomitant maze procedure and intraoperative radiofrequency ablation have been used during the past two decades [1,3]. However, significant concern remains given the inevitable risk of perioperative complications and uncertainty regarding atrial mechanical function [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In this patient collective, the incidence of AF is determined mainly by the underlying cardiac pathology 1 . Surgical therapy of AF added to the indicated cardiac surgical procedure, as a concomitant AF surgery, has been documented to effectively restore sinus rhythm (SR) even in patients with long‐lasting AF 2 . In recent studies, it was shown that the technical modalities to intraoperatively treat AF (surgical cut‐and‐sew maze, modified surgery using radiofrequency ablation, cryo‐ablation) do not influence rhythm success 3 .…”
Section: Introductionmentioning
confidence: 99%